Effect of super absorbent polymer composite on the compressibility behaviour of low plastic clays - Noor Balqish, Mohd Din (2017)
Kaolinite is known to have lower plasticity than any other clay, and it is commonly found in the area of Malaysia. In this study, the usage of kaolin is appropriate since it is one of the commonly found clay in Malaysia. Unlike bentonite, kaolin has low retention of water makes it less commercial in the various fields of the industry, but it can be solves with addition of Super Absorbent Polymer (SAP); a materials with hydrophilic networks that can absorb and retain huge amounts of water or aqueous solution. The physical and chemical properties with or without SAP were studied and suction-water content Soil-Water Characteristic Curve (SWCC) is formed. The techniques used for obtaining the data is using chilled-mirror dew points techniques. Oedometer test also carried out to know the pressure void ratio curve. It shows that there is a potential in increasing the ability of retaining water ability. In conclusion, SAP able to help kaolinite boost their water rate of absorption then enhance the plasticity of the soils.